Semaphorin 7A Promotes VEGFA/VEGFR2-Mediated Angiogenesis and Intraplaque Neovascularization in ApoE-/- Mice - Hu, Shuhong; Liu, Yifei; You, Tao; Zhu, Li (Frontiers in Physiology, 2018)
Excessive neovascularization of atherosclerotic lesions increases plaque vulnerability and the susceptibility to rupture. Semaphorin 7A (Sema7A), a semaphorin family member, was recently reported to promote atherosclerotic plaque formation by mediating d-flow-induced endothelial phenotypic change and leukocyte adhesion. To extend our understanding of the proatherogenic role of Sema7A, we investigated the role of endothelial Sema7A in angiogenesis and atherosclerotic neovascularization. Sema7A overexpression in human umbilical vein endothelial cells (HUVECs) significantly upregulated VEGFA/VEGFR2 and promoted cell migration and angiogenesis. This enhancing effect was eliminated by the blockage of β1 integrin, a Sema7A receptor. Inhibition of FAK or ERK1/2 downstream of β1 integrin signaling significantly inhibited cell migration and angiogenesis via ROCK and MYPT, which are responsible for actin polymerization. Consistently, in vivo studies showed a remarkable reduction in VEGFA/VEGFR2 expression and neovascularization in the atherosclerotic plaques of Sema7A-/-ApoE-/- mice compared to Sema7A+/+ApoE-/- littermates. Supportively, Sema7A deficiency reduced the accumulation of T cells, macrophages, and DCs, and enhanced plaque stability in ApoE-/- mice. Together, our findings indicate that Sema7A promotes VEGFA/VEGFR2-mediated neovascularization in a β1 integrin-dependent manner, supporting a crucial role of Sema7A in the progression of human atherosclerosis.